A review on influence of injection timing and injection pressure on DI diesel engine fuelled with low viscous fuel. (2020) - Gopinath, S.; Devan, P.K.; Mohan, C.; Krishna rao, L.R.; Lokesh kumar, P.; Vara Prasad, S.
Abstract: It is necessary to search for new fuel in an energy crisis considering fuel replacement of diesel fuel considering the emission norms. Also, the rise in demand for fuel is due to the rapid increase of automation in industry and also transportation. At the same time, the disposal of plastic waste is causing serious environmental problems. Waste Plastic Oil (WPO) and renewable energy are getting more attention in this modern world as a source, non-biodegradable alternative. It is observed that most of alcoholic and aromatic fuels are low viscous in nature. The waste plastic oil is associated with gasoline and petroleum products. It is proven that Ethanol and Waste Plastic Oil (WPO) in the compression ignition engines can be used as a supplementary fuel. However, the direct injection diesel engine is designed for diesel fuel, it is necessary to modify the injection pressure and injection timing for low viscous fuel. Thus, consequence of the injection pressure and timing on the Direct Injection Diesel engine was experimentally investigated with low viscous fuel. Tests were carried out at various injection timings like (25°, 23°, 20° and 17° bTDC) and also at reduced injection pressures to find out the least possible emissions and better performance characteristics. Many researchers revealed that retarded injection timing (17°bTDC) and lower injection pressure (180 bar) the low viscous fuel perform well in performance, combustion and emission characteristics.